Emerging Issues in Compensation Valuation for Oil Spillage in the Niger Delta Area of Nigeria - Babawale, Gabriel Kayode (Journal of Reviews on Global Economics, 2013)
Abstract: Oil spillage often impacts substantial land area with grave consequences on the vegetation, economic crops/trees, aquatic life, and the entire eco-system. The impact of oil spills is often widespread and could persists for several years with attendant adverse repercussions on both the health and means of livelihood of people living within the impacted area. For this and other reasons, claims arising from oil spillage often run into billions of naira (N) [1US=N165]. Given the magnitude of the consequential loss and claim, the onus is on the claimant to produce credible evidence to prove that he actually suffered the nature and extent of the injury alleged. This paper reviewed certain fundamental errors that have become commonplace among Nigerian valuers in the discharge of their role of assisting the court to arrive at a just compensation payable for oil spillage in the Niger Delta area of Nigeria. The data used were obtained from valuation reports which the author was privileged to critique as a consultant to a major oil exploration and marketing company in Nigeria. it was found that most of the valuationÂ reports contained flagrant errors and fell short of best practices because less than the required effort is devoted to prosecuting this somewhat complex and highly technical valuation; and more specifically, little attention is paid to the provisions of relevant laws and the standards prescribed by valuation regulatory bodies, which are usually the basis for all statutory valuations.